Penerapan Manajemen Risiko Pembiayaan dalam Meningkatkan Profitabilitas - Mundhori; Fira Isnaini (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2023)
Baitul Maal wat Tamwil (BMT) has an intermediary function. BMT is also tasked with collecting funds from the community and returning it to the community in the form of funds. Procurement of funds for sales entails risks, so funding risk management is required to minimize the occurrence of risks that lead to losses. The study uses a qualitative approach with a kind of case study study, using methods of interviews, observations and documentation to obtain the desired data. Collected data is analyzed by reducing data, presenting data and drawing conclusions. Here are the results of this study: (1) BMT performs her two phases of risk management before the risk occurs and risk management when the risk occurs. (2) The above application by BMT is evidenced by the yearly increase in income.